MENGAJAR VOCABULARY DENGAN MENGGUNAKAN LAGU BERBAHASA INGGRIS DI AKADEMI TEKNIK PERKAPALAN (ATP) VETERAN SEMARANG - Rachmat Ari Wibowo (LP2M, 2018)
Songs have a universal appeal that connects all cultures and languages. Besides having the potential to make lessons interesting and fun, songs as authentic material are very versatile and can be developed into various learning activities. The purpose of English research for cadets is to develop the competence of students in using spoken and written English. In this study qualitative descriptive research was used. The population in this study was 550 cadets of the Shipping Academy (ATP) Veteran Semarang. The sample in this study were cadets majoring in Ship Electrical Engineering (TLK) totaling 36. In this study can be concluded 2 things; the application of English songs to improve English speaking ability and enrich vocabulary is very simple. From the results obtained in this study, proving that the method used is to use English songs to improve the English speaking ability and enrich vocabulary is very effective.Key word: song, teaching English, vocabulary